Ocrelizumab Concentration Is a Good Predictor of SARS‐CoV‐2 Vaccination Response in Patients with Multiple Sclerosis. Issue 1 (2nd November 2022) - van Kempen, Zoé L. E.; Hogenboom, Laura; Toorop, Alyssa A.; Steenhuis, Maurice; Stalman, Eileen W.; Kummer, Laura Y. L.; van Dam, Koos P. J.; Bloem, Karien; ten Brinke, Anja; van Ham, S. Marieke; Kuijpers, Taco W.; Wolbink, Gerrit J.; et al.
Abstract : Ocrelizumab, an anti‐CD20 monoclonal antibody, counteracts induction of humoral immune responses after severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) vaccinations in patients with multiple sclerosis (MS). We aimed to assess if serum ocrelizumab concentration measured at the time of vaccination could predict the humoral response after SARS‐CoV‐2 vaccination. In 52 patients with MS, we found ocrelizumab concentration at the time of vaccination to be a good predictor for SARS‐CoV‐2 IgG anti‐RBD titers after vaccination (comparable to B‐cell count). As the course of ocrelizumab concentration may be predicted using pharmacokinetic models, this may be a superior biomarker to guide optimal timing for vaccinations in B‐cell depleted patients with MS. ANN NEUROL 2023;93:103–108